Factors Related to Subjective Eye Fatigue in Welding Workshop Workers - Yedi Saputra; Ratna Sari Dewi; Ahmad Husaini (Jurnal Ilmu Kesehatan Masyarakat Berkala, 2021)
Welders are at risk of eye fatigue due to exposure to ultraviolet radiation. The district that has the highest number of welding workshops is Kota Baru District, which is 38 welding workshops with 132 workers. The results of the initial survey showed that the most common eye complaints were eye pain, blurred vision, itchy/dry eyes, difficulty in focusing, and decreased eye acuity. The purpose of the study was to determine the factors associated with subjective eye fatigue in welding workshop workers in Jambi City District. The research design used was cross sectional. The sample in this study was a welding workshop worker in Kota Baru District as many as 56 people. This research was conducted in June 2021 at a welding workshop in Kota Baru District. The research instrument is a questionnaire. Data were analyzed by univariate and bivariate using Chi Square test. A total of 64.9% of respondents experienced eye fatigue, 12.3% of respondents did not use Personal Protective Equipment, 70.2% of respondents had a risky working period and 84.2% of respondents had a long risky exposure. Bivariate results show that there is a relationship between the use of Personal Protective Equipment (p-value=0.045), working period (p-value=0.000) and length of exposure (p-value=0.001) with subjective eye complaints in welding workshop workers in Kota Baru Tahun District. 2021. It is expected that workers always use eye protection equipment, namely googles/welding shields during the welding process. Taking short but frequent breaks of 5 minutes 4 times throughout the work time to reduce eye fatigue complaints.